Carabidae (Coleoptera) in agrocenosis of south-eastern Kazakhstan (Experimental biology, 2020)
The article presents the results of field research in 2019-2020 in agrocenoses of South-East Kazakhstan. As a result of the research, 27 species of ground beetles from 9 genera were identified. 1012 beetles from 670 soil traps were registered. The most common of them are types: Harpalus smaragdinus, Harpalus (Psedoophonus) griseus Panzer, 1796, Harpalus (Psedoophonus) rufipes DeGeer, 1774, Poecilus punctulatus Schaller, 1783, Poecilus sericeus sericeus Fischer von Waldheim, 1824, Poecilus versicolor Sturm, 1824, Amara aenea DeGeer, 1774, Calathus (Neocalathus) ambiguus ambiguus Paykull, 1790. The basis of the fauna of agrocenoses is made up of polytopic mesophilic beetles. Irrigated fields are rich in beetles and consist of hygrophils, mesophiles, eurybionts, while most of the beetles are zoophages, as well as mixed (zoophytophagous) and herbivorous (phytophagous) species. Carabidae is the largest group of land beetles in fields and steppe landscapes. Therefore, beetles with a mixed diet are found depending on the environment and air temperature. The complex of beetles in different fields in the study area corresponds to the species of beetles in all fields. During the growing season, the dietary composition of beetles changes: first, predatory beetles prevail, and finally, beetles with a mixed diet.
Keywords: Carabidae, agrocenosis, South-East Kazakhstan, zoophages, zoophytophages, phytophages